“Taking Comedy Seriously”: Humour in Lisa McGee’s Girls and Dolls - María Gaviña-Costero (Estudios Irlandeses, 2024)
Laughter in the midst of tragedy can be one of life’s most disturbing, cathartic and enlightening experiences, a maxim experienced in Northern Ireland during the Troubles, one of the most painful periods of Irish history. Northern Irish playwrights were acutely aware of this when dealing with violence in their plays and so, however grim the events they depicted, the comic element was very much present. After the Good Friday Agreement, along with the change in the political situation in Northern Ireland, there was a generational change in the theatre. What seems to characterise this new wave is the ironic distance taken towards the sectarian divide and the consequences of the conflict on Northern Irish society, which is revealed above all in their use of humour. Lisa McGee, one of the most important representatives of the new generation thanks to the popularity of her television series Derry Girls, had already shown her maturity in her 2006 play Girls and Dolls, performed by Tinderbox the same year. McGee mixes the tragic and the comic to present the terrible consequences of childhood trauma alongside the violence of the late Troubles, while raising questions about guilt, the meaning of friendship and the subtle ways in which violence affects us. This article aims to analyse the different uses of humour employed by McGee to deal with tragic episodes and their theatrical effect, drawing on the existing research on humour in literature and McGee’s own observations given in an interview with the author on 3 March 2023.